2020
DOI: 10.5223/pghn.2020.23.5.457
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors and Nutritional Profiles Associated with Stunting in Children

Abstract: Purpose: To analyze risk factors and various nutrients associated with stunting among children aged 6-60 months. Methods: This is a case-control and cross-sectional study between 40 stunting cases and 40 controls. Data on possible risk factors associated with stunting were obtained through direct interviews and using a questionnaire. Examination of vitamin D, zinc, albumin, and ferritin levels was performed on both groups. Data were analyzed using IBM SPSS Statistics for Windows, Version 23.0 (IBM Co., Armonk,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 13 publications
(23 reference statements)
1
5
0
1
Order By: Relevance
“…The study showed that prevalence of stunting children was more common among male than female children but statistically was not significant. This founding similar to other studies that documented boys more common than girls in the prevalence of stunted children [12], [13], [14]. To date, it is unclear what social or biological reason might account for this difference [14].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The study showed that prevalence of stunting children was more common among male than female children but statistically was not significant. This founding similar to other studies that documented boys more common than girls in the prevalence of stunted children [12], [13], [14]. To date, it is unclear what social or biological reason might account for this difference [14].…”
Section: Discussionsupporting
confidence: 91%
“…Lower maternal height in our study was found to be a significant factor associated with stunted children. A study also found that maternal height <150 cm coincided with maternal age at high risk, low birth weight, and body length were strongly associated with stunting [12]. Beal reports that lower maternal height along with lower maternal education are important determinants of child stunting in Indonesia [6].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The proportion of participants with calcium deficiency was higher in severely thin/thin category. A study from Indonesia, reported that level of calcium and vitamin D were not associated with the incidence of stunting [ 70 ]. Another study on Ecuadorian children reported that low serum vitamin D levels in underweight and stunted [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…History of LBW had a significant effect on the incidence of stunting with (OR= 10.44;95%CI= 3.28 to 33.30;p< 0.001). A study aimed to analyze risk factors and various nutrients associated with stunting among children aged 6-60 months, found that LBW is the main risk factor contributing to stunting and is strongly associated with low zinc levels (Febriani et al, 2020). Another study showed that LBW was a predictor of stunting in children aged 0-11 months (Sartika et al, 2021).…”
Section: Discussionmentioning
confidence: 99%